Molecular characterization and phylogenetic analysis of outer membrane protein p2 (OMPP2) of Glaesserella (Haemophilus) parasuis isolates in Central State of Peninsular Malaysia - Lee, Chee Yien; Ong, Hui Xin; Tan, Chew Yee; Low, Suet Ee; Phang, Lai Yee; Lai, Jyhmirn; Ooi, Peck Toung; Fong, Michelle Wai Cheng (Multidisciplinary Digital Publishing Institute, 2023)
Glaesserella (Haemophilus) parasuis, the etiological agent of Glässer’s disease, is an economically significant pathogen commonly associated with serofibrinous polyserositis, arthritis, fibrinous bronchopneumonia and/or meningitis. This study is the first attempt to molecularly characterize and provide a detailed overview of the genetic variants of G. parasuis present in Malaysia, in reference to its serotype, virulence-associated trimeric autotransporters (vtaA) gene and outer membrane protein P2 (OmpP2) gene. The G. parasuis isolates (n = 11) from clinically sick field samples collected from two major pig producing states (Selangor and Perak) were selected for analysis. Upon multiplex PCR, the majority of the isolates (eight out of 11) were identified to be serotype 5 or 12, and interestingly, serotypes 3, 8 and 15 were also detected, which had never been reported in Malaysia prior to this. Generally, virulent vtaA was detected for all isolates, except for one, which displayed a nonvirulent vtaA. A phylogenetic analysis of the OmpP2 gene revealed that the majority of Malaysian isolates were clustered into genotype 1, which could be further divided into Ia and Ib, while only one isolate was clustered into genotype 2.